2011
DOI: 10.1128/jvi.00693-11
|View full text |Cite
|
Sign up to set email alerts
|

Absence of XMRV Retrovirus and Other Murine Leukemia Virus-Related Viruses in Patients with Chronic Fatigue Syndrome

Abstract: Chronic fatigue syndrome (CFS) is a multisystem disorder characterized by prolonged and severe fatigue that is not relieved by rest. Attempts to treat CFS have been largely ineffective primarily because the etiology of the disorder is unknown. Recently, CFS has been associated with xenotropic murine leukemia virus-related virus (XMRV) as well as other murine leukemia virus (MLV)-related viruses, though not all studies have found these associations. We collected blood samples from 100 CFS patients and 200 self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 26 publications
(46 reference statements)
5
65
0
2
Order By: Relevance
“…XMRV was also reported to be presence in patients with chronic fatigue syndrome (CFS) (Lombardi et al, 2009). However, the link between XMRV and CFS is unclear, because in other studies it has failed to detect XMRV infection in CFS patients Groom et al, 2010;Switzer et al, 2010;van Kuppeveld et al, 2010;Knox et al, 2011;Satterfield et al, 2011;Shin et al, 2011). However, gammaretroviruses are known to induce cancer in animals, understanding XMRV or related MLV infections in human prostate cancer tissues will shed light on their potential contribution to human disease.…”
Section: Introductionmentioning
confidence: 99%
“…XMRV was also reported to be presence in patients with chronic fatigue syndrome (CFS) (Lombardi et al, 2009). However, the link between XMRV and CFS is unclear, because in other studies it has failed to detect XMRV infection in CFS patients Groom et al, 2010;Switzer et al, 2010;van Kuppeveld et al, 2010;Knox et al, 2011;Satterfield et al, 2011;Shin et al, 2011). However, gammaretroviruses are known to induce cancer in animals, understanding XMRV or related MLV infections in human prostate cancer tissues will shed light on their potential contribution to human disease.…”
Section: Introductionmentioning
confidence: 99%
“…This finding has raised speculation that it may cause the syndrome. However, four other laboratories could not replicate this finding, whilst four new studies found it only as a laboratory contaminant (Calaway, 2011;Cohen, 2011;Kaiser, 2011;Schutzer et al, 2011;Shin et al, 2011;Kean, 2010;Mayor, 2010;Sato et al, 2010;Stoye et al,2010;Coffin & Stoye, 2009). In 2011, at a retrovirology meeting in Boston, Massachusetts, researchers presented evidence that this retrovirus is, in effect, a laboratory artefact and not a human pathogen.…”
Section: Other Rna Virusesmentioning
confidence: 97%
“…In der Mehrzahl der später veröffentlich-ten Studien wurde XMRV jedoch in keiner einzigen Probe nachgewiesen [8,9,10,11,12,13]. Bei Wiederholungsuntersuchungen von zuvor am WPI im Rahmen der initialen Studie [3] positiv getesteten CFS-Patienten konnten in unabhängigen Laboren in keinem einzigen Fall XMRV oder spezifische Antikörper gegen XMRV-Proteine nachgewiesen werden, obwohl nahezu identische, hochsensitive Verfahren verwendet wurden [14,15]. Hiermit stellt sich die Frage, was die Ursache für den beschriebenen Nachweis von XMRV am WPI und an einem kommerziellen Labor sowie in den anderen Studien sein könnte.…”
Section: Ursprüngliche Einschätzung Von Xmrv Als Neues Retrovirus Mitunclassified
“…Mehrere Arbeitsgruppen, die positive XMRV-Befunde erhalten hatten, konnten zeigen, dass ihre positiven Ergebnisse auf Kontaminationen mit muriner genomischer DNA zurückzuführen sind [16,17]. Die Quelle der Verunreinigung konnte in einigen Fällen identifiziert werden [15]. In DNA-Extraktionssäulen und in kommerziellen Polymerasepräparationen wurden Spuren muriner DNA nachgewiesen, die möglicherweise durch monoklonale Antikörper bei Reinigung der Polymerase eingebracht wurden [18,19].…”
Section: Kontaminationen Als Quelle Positiver Xmrv-befundeunclassified